Effects of chromophore interaction in the spectroscopy of ketocyanine dyes with a central pyranone or pyridone fragment - Ludmila A. Shvedova; Alexander S. Tatikolov; Vladimir I. Sklyarenko; Zhanna A. Krasnaya (International Journal of Photoenergy)
The study is devoted to investigation of a number of ketocyanine dyes (polyenic ω,ω′-bisaminoketones) with a central pyranone or pyridone fragment and respective polymethine salts by UV-VIS absorption and NMR spectroscopies. It was found that replacement of bridging O atom with NMe group suppresses the chromophore interaction in the cross-conjugated ketone and corresponding tridecamethine salt. Furthermore, incorporation of meso-amino substituent into the polymethine chain of the salts with the central pyrylium fragment sharply decreases the chromophore interaction. In spite of dramatic differences between the absorption spectra of the ketocyanines containing O- or NMe- bridging fragment, 13C NMR spectra of these dyes are similar. A comparison of the differences between the chemical shifts of adjacent polymethine carbon atoms in the 13C NMR spectra for these dyes point to stronger alternation of charges along the polymethine chain and, consequently, stronger chromophore interaction for the dye with the central pyrylium cycle. Flash photolysis experiments showed photoisomerization of the dyes with NMe bridging group to form long-lived isomeric form.